Abstract 064: The Pushability of Commonly Used Microwires in Neuroendovascular Procedures - Amir Molaie; Keiko A Fukuda; Kenichi Sakuta; Kentaro Suzuki; Mahsa Ghovvati; Naoki Kaneko; Omar Selim; Satoshi Tateshima; Taichiro Imahori; Yoshiki Hanaoka (Stroke: Vascular and Interventional Neurology)
Introduction In distal and medium‐vessel occlusions (DMVOs), there are increasing opportunities to deliver devices through tortuous and medium sized arteries. However, this comes at the risk of microwire perforation during distal microcatheter advancement for navigation in these curved, slender vessels, leading to hemorrhagic complications. Currently, microwires with a range of stiffness levels are available. However, it is unclear how the variations in stiffness and the relative positioning of the microwire and microcatheter may affect the force applied to the vessel wall. Few studies have compared objective metrics across different commonly used devices. We sought to compare the pushability of various Synchro Select and Chikai microwires using both proximal and distal support. Methods In a moderate tortuosity, silicone flow model of the middle cerebral artery (MCA) branches, we tested 0.014” nitinol microwires (Synchro Select Soft, Standard, or Support), or 0.014” stainless steel microwires (Chikai, Black, and Black Soft) in a TrevoTrak 21 microcatheter docked either in the proximal M1 segment or distal M2 segment. Applied force was measured using an Imada force gauge DST‐1A at the M2 ten times for each experiment. The slope, measured in mN per mm, of the applied distal force during the maximal pushing period was calculated. Results The average slope of the pushing force within a distal microcatheter was 10.64 mN/mm with a Synchro Soft, 10.85 mN/mm with a Standard, and 15.28 mN/mm with a Support microwire (p < 0.0001). The average slope of the pushing force in a proximal microcatheter was 1.61 mN/mm with a Synchro Soft, 3.15 mN with a Synchro Standard, and 3.87 mN with a Synchro Support microwire (p <0.001). With the Chikai microwires, the average slope of the pushing force within a distal microcatheter was 12.48 mN/mm with a Chikai Black Soft wire, 12.82 mN/mm with a Chikai Black microwire, and 14.11 mN/mm using a Chikai microwire (p=0.801). Within a proximal microcatheter, the average maximal force was 2.42 mN/mm using a Chikai Black Soft wire, 3.16 mN/mm using Chikai Black, and 3.91 mN/mm using the Chikai wire (p < 0.001). Conclusion This study demonstrated that stiffer microwires push the arterial wall with significantly greater force within a microcatheter close to the wall. Pushability of the microwire significantly dropped across all microwires when the microcatheter was positioned more proximally. This is the first known report of the pushability of commonly used microsystems in neuroendovascular procedures.